Rural Violence in Obudu and Vandeikya Communities: Paths to Conflict Resolution - Terwase, Isaac Terungwa; Tor Tsuwa, John; Siben Nfor, Eric; O. Itoje-Akpokiniovo, Lilian; Mary Yvonne Atime, Shimenenge; Bitrus Nuhu, Mailabari; Bala Kachalla, Lummo; Onyekachi Onwuanibe, Jude; Manu, Hammadu; Mikaila, Safwan; Olatunji Sowore, Julius; Mijinyawa, Aaron; et al. (Kashere Journal of Politics and International Relations, 2023)
The rural areas in Nigeria are mostly known for agricultural productions which are basically carried out by the farmers in the rural settlements. This paper is focused on the rural violence and farmers clashes between the people of Obudu and Vandeikya Communities in Cross River and Benue States respectively. The objective of the study is to identify the root causes of the said conflict, the strategies used in the past and its failed attempts in handling the conflict over land disputes. The study adopts the use of qualitative research design through the conduct of interviews. The article therefore, proffers a holistic approach to conflict resolution on the said disputes among the farmers in the two communities. The research recommends urgent attention by the Federal Government of Nigeria on the disputed land to put beacons that would demarcates the boundary between the two communities (Obudu and Vandeikya) so as to resolve the conflict.